2005
DOI: 10.1080/00071660400023813
|View full text |Cite
|
Sign up to set email alerts
|

Use of the range area in organic egg production systems: effect of climatic factors, flock size, age and artificial cover

Abstract: (1) To evaluate the effect of climate, flock size, age and artificial cover on the use of range area, a study was conducted in 1994 to 1998, involving 5 farms with a total of 37 flocks of layers kept in commercial, free-range, organic systems. Flocks were visited regularly during the production period to record the number and distribution of hens on the range. (2) On average 9% of the flock used the range area, but with large variations both within and between flocks, and this was partly influenced by climatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
103
5
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 12 publications
17
103
5
2
Order By: Relevance
“…Anecdotal evidence from feed compounders indicates that larger flock sizes of 1000 or more birds in organic systems are particularly prone to cannibalism and that this occurs because, unlike smaller flocks, they are unable to cope with inadequate diets by obtaining additional nutrients from the range environment. Data from this study and previous reports (Hegelund et al, 2005) support the view that smaller flocks utilise the range well and more efficiently than larger flocks. In this study, the relatively low concentration of sulphur amino acids in the diets, which appears to have an over-riding effect on growth, appears to be compensated for, at least in part, by the ability of the birds to scavenge extra feed material.…”
Section: Discussionsupporting
confidence: 88%
“…Anecdotal evidence from feed compounders indicates that larger flock sizes of 1000 or more birds in organic systems are particularly prone to cannibalism and that this occurs because, unlike smaller flocks, they are unable to cope with inadequate diets by obtaining additional nutrients from the range environment. Data from this study and previous reports (Hegelund et al, 2005) support the view that smaller flocks utilise the range well and more efficiently than larger flocks. In this study, the relatively low concentration of sulphur amino acids in the diets, which appears to have an over-riding effect on growth, appears to be compensated for, at least in part, by the ability of the birds to scavenge extra feed material.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to fearfulness, range use seems to be dependent on a number of other variables. These may include birds' previous experience with the environment and the outdoor range (Grigor et al, 1995;Janczak and Riber, 2015), pop-hole size, accessibility to the range (Gilani et al, 2014), and structures on the range (Hegelund et al, 2005;Rault et al, 2013). In the present experiment, the range areas were fenced off and had wire mesh across the top; hence the birds were protected from predators.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of studies in this area report much lower range use. Hegelund et al (2005) studied flocks ranging from 513 to 6000 hens, and found that an average of 9% of hens used the range area, with large variations within and between flocks. Hegelund et al (2006) reported that an average of 18% of hens used the outdoor range area in flocks of 1200 to 5000 hens, and Dawkins et al (2003) found a maximum of <15% of the total flock accessing the range area during the day, using in situ behaviour observations of broiler chickens on commercial farms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not, however, proportional to group size as a smaller proportion of birds were seen on the veranda in the larger groups. A decreasing percentage of birds go outside with increasing flock size (Hegelund et al, 2005), which has also been found in smaller flocks comprising 250, 500 and 1000 birds (Harlander-Matauschek, 2001). In terms of number of birds, however, both these studies showed more birds outside as flock size increased.…”
Section: Discussionmentioning
confidence: 83%